Analisis Kesulitan Belajar Siswa pada Mata Pelajaran Fikih di Kelas X MA Sunan Ampel Kediri - Al Hariri, M. Ibnu Annaufal; Hidayah, Nurul; Chotimah, Chusnul (YASIN, 2025)
The limited number of studies on student learning difficulties in fiqih subjects at pesantren-based madrasahs forms the background of this research, given its significant impact on academic achievement and learning motivation. This study aims to analyze the forms of learning difficulties experienced by tenth-grade students at MA Sunan Ampel Kediri, identify their contributing factors, and formulate effective intervention strategies. A descriptive qualitative method was employed, involving Grade X students, fiqih teachers, and the school principal, selected through purposive sampling. Data were collected via observation, interviews, and documentation, and analyzed through data reduction, data display, and verification using triangulation. The findings reveal two primary forms of learning difficulties: learning disabilities, driven by internal factors such as low motivation, interest, and readiness to learn; and learning disorders, influenced by social pressure from peers. Symptoms include declining grades, passive classroom behavior, and a tendency to lower academic performance to conform to peer groups. Intervention strategies by fiqih teachers include varied teaching methods, group discussions, the use of contextual examples, and personalized approaches. At the institutional level, programs such as syawir (student forums), strengthening of classical texts through Madrasatul Qur’an, and academic competitions function as systematic interventions to foster a more positive learning environment. The study concludes that a holistic approach integrating academic, social, and spiritual dimensions is essential. Its implications contribute to the literature on learning difficulties in madrasahs and offer practical recommendations for teachers and educational institutions in designing adaptive learning strategies and sustainable support programs.